(untitled) (Al-Qamar, 2024)
Women’s right to inheritance is established and protected by Islam. Pakistan, as an Islamic country, expects its citizens to obey all of the principles enshrined in the Holy Quran and Sunnah. However, in case of inheritance to women, people often deviate from these guidelines. Although many efforts are in progress to augment the social and economic status of women in this country, despite that malafide practice persists in this society where Pakistani women, before or at the time of marriage, are compelled, due to undue influence, to surrender their inheritance in favor of their brothers. This systemic exclusion of women from inheritance happens through the transfer of property using the guise of gift. Even though courts in the country are cognizant of this practice and are actively trying to tackle it through their judgments, yet their efforts alone are insufficient. In these circumstances, what this society needs are amendments in both criminal and civil laws to unambiguously prohibit the deprivation of women from their rightful inheritance. Additionally, it is also the legal as well as moral duty of every